Song from the Bohohlasnyk «When the Soul is Separated from the Body»: Sources and Textual Aspects - Zosim, O. L (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. Among the works of the Bohohlasnyk, one of the most popular is the song “When the soul is separated from the body”. It was known to Ukrainian believers even before the Bohohlasnyk was published, thanks to its widespread circulation in manuscript songbooks. Due to its theological, literary and musical value, the song was included in the first Ukrainian cantional, which is the Pochaiv edition, and thanks to this it became part of the national spiritual song canon. The purpose of the article is to conduct a comprehensive study of the song “When the soul is separated from the body” in its historical path from the original source to the codified version in the Bohohlasnyk. The methodological basis of the article was, in addition to source-meaning-textual methods, historical-cultural, analytical, comparative and heuristic methods, which made it possible to comprehensively consider different versions of the song “When the soul is separated from the body” and trace its textual and melodic transformations in historical dynamics. The results and conclusions. The text of the song “When the soul is separated from the body” refers not only to Ukrainian baroque poetry with motifs of memento mori and vanitas vanitatum, but also to church hymnography. The incipit of the song is taken from the text of the canon included in the Order of the Departure of the Soul (Ἀκολουθία εἰς Πυχορραγοῦντα), and its content is concentrated on the key moments of the hymnographic primary source, at the same time the author strengthens the moral and instructive orientation. The melody of the song “When the soul is separated from the body” has Polish origins. The work is a textual and melodic contrafactum of the song “I am already leaving you, sweet child”, which is an adapted translation of the Polish planctus song “Już Cię żegnam, najmilszy Synu Jezusie”. When preparing the work for publication, the editors of the Bohohlasnyk made a literary revision of it, which did not affect the content and formal features, however, these changes a clear separation the pre-Bohohlasnyk and post-Bohohlasnyk versions of text. The themes of the songs “I am already leaving you, sweet child” and “When the soul is separated from the body” are not related, but since the theme of death is central in both works, it was this that inspired the author of the latter to turn to the translation of the Polish planctus as a textual and melodic model. The analysis of melodic variants from the mid-18th century manuscript and the Bohohlasnyk showed the kinship of the melodies of the songs “I am already leaving you, sweet child” and “When the soul is separated from the body”, and also revealed melodic transformations that arose in the process of existence, in which we observe a tendency to maximally assimilate the contrasting parts of the melody of the original. In the version of the song “When the soul is separated from the body” from the Bohohglasnyk, we see not only a smoothing of contrasts, but also its approximation to the sound of Ukrainian church monody, thereby more closely linking it with the text, which is based on Eastern Christian church hymnography